Improved Learning in U.S. History and Decision Competence with Decision-Focused Curriculum - Jacobson, David; Parker, Andrew; Spetzler, Chris; Bruin, Wandi Bruine de; Hollenbeck, Keith; Heckerman, David; Fischhoff, Baruch (PLoS ONE, 2012)
Decision making is rarely taught in high school, even though improved decision skills could benefit young people facing life-shaping decisions. While decision competence has been shown to correlate with better life outcomes, few interventions designed to improve decision skills have been evaluated with rigorous quantitative measures. A randomized study showed that integrating decision making into U.S. history instruction improved students’ history knowledge and decision-making competence, compared to traditional history instruction. Thus, integrating decision training enhanced academic performance and improved an important, general life skill associated with improved life outcomes.